Portugal : Fifth Review Under the Extended Arrangement and Request for Waivers of Applicability and Nonobservance of End-September Performance Criteria: Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Portugal. (IMF Staff Country Reports; Country Report, 2012)
The staff report for the Fifth Review Under the Extended Arrangement and Request for Waivers of Applicability and Nonobservance of End-September Performance Criteria, prepared by a staff team of the IMF, following discussions that ended on September 11, 2012, with the officials of Portugal on economic developments and policies. Based on information available at the time of these discussions, the staff report was completed on October 15, 2012. The views expressed in the staff report are those of the staff team and do not necessarily reflect the views of the Executive Board of the IMF.